Digestible energy content of corn- vs sorghum-based dried distillers grains with solubles and their effects on growth performance and carcass characteristics in finishing pigs - C Feoli; C Monge; Terry L Gugle; S D Carter; N A Cole; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2007)
Two experiments were conducted to determine the nutritional value of corn- and sorghum-based dried distillers grains with solubles (DDGS). In Exp. 1, 120 finishing pigs (average initial weight of 244 lb) were used in a 19-d DE determination. The reference diet was 97% corn with vitamins, minerals, and amino acids added to meet or exceed all NRC suggested nutrient concentrations. Treatments were corn-based (Sioux River Ethanol, Hudson, SD and MGP Ingredients, Atchison, KS) and sorghum-based (US Energy Partners, Russell, KS and Western Plains Energy, Oakley, KS) DDGS substituted as 50% of the reference diet in place of corn. Comparisons among the treatments indicated that DDGS from corn had 101 kcal/lb greater DE than DDGS from sorghum (P0.58) and percentage carcass lean (P>0.25) were not affected by treatment. In conclusion, plant of origin and substrate used in the fermentation process (corn vs sorghum) affected the nutritional value of DDGS for finishing pigs.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; DDGS; Feed ingredient; Meat quality; Sorghum